EFEKTIVITAS IMPLEMENTASI KEBIJAKAN PENGELOLAAN LINGKUNGAN DI WILAYAH KEPESISIRAN SENDANG BIRU KECAMATAN SUMBER MANJING WETAN KABUPATEN MALANG - , PEGGY PUSPA HAPSARI, S.SOS ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Sendang Biru is a coastal area that has a lot of potential with the utilization of a diverse nature. This study examines the environmental policies implemented by the stakeholders in the Sendang Biru Coastal Area. In fact the utilization of the Sendang Biru Coastal Area is quite complex with the involvement of many stakeholders. The purpose of this study is to assess the effectiveness of the implementation of management policies in the Sendang Biru Coastal Area, find the factors that influence the effectiveness of the implementation of management policies in the Sendang Biru Coastal Area and formulate appropriate strategies and environmental management can be implemented in Sendang Biru Coastal Area. The research method uses survey research methodology. Survey research using interview techniques with guide questions using an instrument (questionnaire). In addition to the required data obtained from the study of literature, documentation, and field observations. The results showed that the level of effectiveness of policy implementation of the Blue Spring area management categories 'Very Effective' at 59.47%, the category of 'Simply Effective' by 35.1% and 'Less Effective' at 5.4%. It can be said that the level of effectiveness of the implementation environmental management policies Sendang Biru Coastal Area is very effective. Factors affecting the high value of the effectiveness of implementation policies is availability of adequate financial program for financing operational activities. Environmental management strategies of Sendang Biru Coastal Area is in an integrated management, by assembling a management plan that synergy by involving all relevant stakeholders.